Implementasi perancangan integrasi IE matrix balanced scorecard dalam penilaian kinerja bisnis salad sayur (Studi kasus: InaGreen Farm – Kabupaten Bandung Barat) - Riswandi, Dadang Iwan; Anisya, Syahrani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
InaGreen Farm is a company engaged in horticultural vegetables. InaGreen Farm is a producer and supplier of vegetables to retailers in Bandung City. In 2023 InaGreen Farm established a vegetable salad business unit by utilizing excess product stock to develop its business to increase company profits. The marketing carried out by the company in marketing vegetable salad products is Business to Consumer. InaGreen Farm in developing a business can certainly increase profits by paying attention to performance in terms of financial and non-financial aspects. Performance evaluation is an important component in assessing the success of company operations. One very important component in assessing the operational success of an organization is performance evaluation. InaGreen Farm needs to measure performance using performance measurement through Balanced Scorecard analysis with the help of Expert Choice 11 software. The results of InaGreen Farm’s performance measurement research have a total performance score of 93% with a very good category (AA). InaGreen Farm merupakan perusahaan yang bergerak pada sayuran hortikultura. InaGreen Farm menjadi produsen dan pemasok sayuran ke ritel-ritel di Kota Bandung. Pada tahun 2023, InaGreen Farm mendirikan unit bisnis salad sayur dengan memanfaatkan kelebihan stok produk untuk mengembangkan usahanya untuk meningkatkan profit perusahaan. Pemasaran yang dilakukan perusahaan dalam memasarkan produk salad sayur, yaitu dengan Business to Consumer. InaGreen Farm dalam mengembangkan bisnis tentunya dapat meningkatkan profit dengan memperhatikan kinerja dari segi keuangan dan non-keuangan. Evaluasi kinerja adalah komponen penting dalam menilai kesuksesan operasional perusahaan. Salah satu komponen yang sangat penting dalam menilai kesuksesan operasional suatu organisasi adalah evaluasi kinerja. InaGreen Farm perlu mengukur kinerja menggunakan pengukuran kinerja melalui analisis Balanced Scorecard dengan bantuan software Expert Choice 11. Hasil penelitian pengukuran kinerja InaGreen Farm memiliki total skor kinerja 93% dengan kategori sangat baik (AA).